Risk prediction in patients with classical low-flow, low-gradient aortic stenosis undergoing surgical intervention - Tessari, Fernanda Castiglioni; Lopes, Maria Antonieta Albanez A. de M.; Campos, Carlos M.; Rosa, Vitor Emer Egypto; Sampaio, Roney Orismar; Soares, Frederico José Mendes Mendonça; Lopes, Rener Romulo Souza; Nazzetta, Daniella Cian; de Brito Jr, Fábio Sândoli; Ribeiro, Henrique Barbosa; Vieira, Marcelo L. C.; Mathias, Wilson; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Classical low-flow, low-gradient aortic stenosis (LFLG-AS) is an advanced stage of aortic stenosis, which has not only a poor prognosis with medical treatment but also a high operative mortality after surgical aortic valve replacement (SAVR). There is currently a paucity of information regarding both the current prognosis of classical LFLG-AS patients undergoing SAVR, as well as the lack of a reliable risk assessment tool for this particular subset of AS patients. The present study aims to assess mortality predictors in a population of classical LFLG-AS patients undergoing SAVR. Methods: Prospective study including 41 consecutive classical LFLG-AS patients (aortic valve area≤1.0cm², mean transaortic gradient<40mmHg, left ventricular ejection fraction <50%). All patients underwent dobutamine stress echocardiography (DSE), 3D echocardiography, and T1-mapping cardiac magnetic resonance (CMR). Patients with pseudo-severe aortic stenosis were excluded. Patients were divided in groups according to the median value of the mean transaortic gradient (≤25mmHg and >25mmHg). All-cause mortality, intraprocedural, 30-day and 1-year mortality were evaluated. Results: All of the patients had degenerative aortic stenosis, with a median age of 66 [60-73] years, most of them being male (83%). The median EuroSCORE II was 2.19 (1.5-4.78)% and the median STS was 2.19 (1.6-3.99)%. On DSE, 73.2% had flow reserve (FR), i.e. an increase in stroke volume≥20% during DSE, with no significant differences between groups. On CMR, late gadolinium enhancement mass was lower in the group with mean transaortic gradient>25 mmHg (2.0 [0.0-8.9] vs 8.5 [2.3-15.0]g; p=0.034), and myocardium extracellular volume fraction (ECV) and indexed ECV were similar between groups. The 30-day and 1-year mortality were 14.6% and 43.8%, respectively. Median follow-up was 4.1 [0.3-5.1] years. By multivariate analysis adjusted for FR, only mean transaortic gradient was an independent predictor of mortality (HR:0.923, 95% CI 0.864-0.986, p=0.019). A mean transaortic gradient≤25mmHg was associated to higher all-cause mortality rates (log-rank p=0.038), while there was no difference in mortality regarding FR status (log-rank p=0.114). Conclusions: In patients with classical LFLG-AS undergoing SAVR, mean transaortic gradient was the only independent mortality predictor in patients with LFLG-AS, specially if ≤25mmHg. The absence of left ventricular FR had no prognostic impact on long-term outcomes.